2022
DOI: 10.1007/s00217-022-04049-0
|View full text |Cite
|
Sign up to set email alerts
|

Analytical evaluation of carotenoids, apocarotenoids, capsaicinoids, and phenolics to assess the effect of a protective treatment on chili peppers dried at different temperatures

Abstract: The most common preservation process for chili peppers is drying, which inevitably causes oxidative degradation of thermolabile molecules. The aim of this research was to evaluate the potential protective effect exerted by an active ingredient based on grape seed oil, on pepper fruits. Grapeseed oil is rich in antioxidant compounds and was applied to pepper’s surface in form of a sol–gel product, before fruit thermal treatment. In this work, chili peppers samples were preventively treated with an active soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Liu et al ( 29 ) reported high total phenolic content in CPSs (3.93-6.21 mg GAE/g) using methanol, ethanol, or acetone but no information about the yield was described. Grimaldi et al characterized extracts from Capsicum annum fruits dried at different temperatures (45-65°C) and showed that the TPC decreased meanwhile the temperature increased from 6.9 mg GAE/g (45°C) to 6 mg GAE/g (65°C), in concordance with our results that the TPC equally decreased with the increasing of the temperature of extraction due the oxidation of phenolic compounds ( 30 ). Regarding seeds, Leng et al showed the total phenolic content of Australian growth bell pepper seeds and demonstrated that the variety of bell pepper did not affect the phenolic contents of extracts from the seeds (0.43-0.53 mg GAE/g), in contrast with our results in this research demonstrated that the use of EAE improved significantly the TPC of CPS extracts ( 31 ).…”
Section: Resultssupporting
confidence: 91%
“…Liu et al ( 29 ) reported high total phenolic content in CPSs (3.93-6.21 mg GAE/g) using methanol, ethanol, or acetone but no information about the yield was described. Grimaldi et al characterized extracts from Capsicum annum fruits dried at different temperatures (45-65°C) and showed that the TPC decreased meanwhile the temperature increased from 6.9 mg GAE/g (45°C) to 6 mg GAE/g (65°C), in concordance with our results that the TPC equally decreased with the increasing of the temperature of extraction due the oxidation of phenolic compounds ( 30 ). Regarding seeds, Leng et al showed the total phenolic content of Australian growth bell pepper seeds and demonstrated that the variety of bell pepper did not affect the phenolic contents of extracts from the seeds (0.43-0.53 mg GAE/g), in contrast with our results in this research demonstrated that the use of EAE improved significantly the TPC of CPS extracts ( 31 ).…”
Section: Resultssupporting
confidence: 91%
“…Natural preservatives like lemon essential oil preserved total capsaicinoids, phenolics, antioxidant activity, and carotenoids in Habanero pepper paste while thermal processing can affect the color properties . Pretreatment of pepper fruits with grapeseed oil before drying at higher temperatures can prevent oxidative loss of capsaicinoids and carotenoids and can improve shelf life . Ozone-assisted degradation of pesticides at the rate of 5.5 g h –1 did not affect capsaicin content and color in dry chilies .…”
Section: Postharvest Treatment For Maximum Retention Of Secondary Met...mentioning
confidence: 97%
“…192 Pretreatment of pepper fruits with grapeseed oil before drying at higher temperatures can prevent oxidative loss of capsaicinoids and carotenoids and can improve shelf life. 193 Ozone-assisted degradation of pesticides at the rate of 5.5 g h −1 did not affect capsaicin content and color in dry chilies. 194 Chlorine dioxide (30 μL L −1 ) treatment of harvested green chili peppers reduced chlorophyll degradation rate and carotenoid biosynthesis via down regulating chlorophyll breakdown genes and carotenoid pathway genes, respectively.…”
Section: Postharvest Treatment For Maximum Retention Of Secondary Met...mentioning
confidence: 99%